2022
DOI: 10.1371/journal.pone.0262866
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic evaluation of pectus excavatum in 14 cats

Abstract: Pectus excavatum (PE) is one of the most frequently reported chest deformities. However, limited studies are available with regard to its CT scan findings in cats. In the present research computed tomographic images of the thoraxes of 14 cats diagnosed with PE has been reviewed. This is one of the first studies exploring the use of CT to characterise PE in animals. The aim of this study was to present characteristic CT features of PE in cats. The introduction of new criteria for better assessing thoracic wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A large proportion (67%) of affected cats in our study population had an atypical location of pectus excavatum, in which the dorsal deviation affects the cranial and mid-section of the sternum. This was also reported in a recent publication on computed tomographic features of pectus excavatum in cats, in which half the cats had the atypical form of the disorder [ 11 ]. That study found mild pectus excavatum in only 21.5% of cats, whilst most of the cats included had moderate or severe pectus excavatum.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…A large proportion (67%) of affected cats in our study population had an atypical location of pectus excavatum, in which the dorsal deviation affects the cranial and mid-section of the sternum. This was also reported in a recent publication on computed tomographic features of pectus excavatum in cats, in which half the cats had the atypical form of the disorder [ 11 ]. That study found mild pectus excavatum in only 21.5% of cats, whilst most of the cats included had moderate or severe pectus excavatum.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, computed tomography would allow a better representation of the anatomy. For instance, computed tomography was reported to be useful for evaluation of thoracic asymmetry and sternal torsion in cats with pectus excavatum, which cannot be done with radiography [ 11 ]. In addition, the use of intravenous iodinated contrast medium in computed tomography would allow for better characterization of potential soft tissue abnormalities, such as inflammation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations